Crystal-Storing Histiocytosis in Bone Marrow: A Clinicopathologic Study of Eight Cases and Review of the Literature. Issue 2 (29th January 2018) - Fang, Hong; Chiu, April; Reichard, Kaaren K
Abstract: Objectives: We report the clinicopathologic characteristics of eight cases of crystal-storing histiocytosis (CSH) with bone marrow (BM) involvement (BM-CSH) and review CSH cases published in the English literature. Methods: We queried our pathology database for BM cases with CSH mentioned in the final diagnosis/comments from June 2011 to August 2016. Results: Eight cases of BM-CSH were identified. The underlying diagnoses consisted predominantly of plasma cell disorders (88%) associated with monotypic κ light chain. In BM aspirates, crystals within histiocytes exhibited a morphologic spectrum including brightly eosinophilic, needle-like, or globule-like. In BM core biopsies, the histiocytes were often in aggregates with intracellular needle-like and/or globular, refractile inclusions. Conclusions: BM-CSH is a rare phenomenon and exhibits a heterogeneous crystalline and histiocytic appearance warranting accurate recognition to avoid misinterpretation of a granulomatous condition or storage disorder. In addition, prompt assessment for an underlying B-cell lymphoma or clonal plasmacytic neoplasm is indicated.